Análisis de la gestión recaudadora de la cartera de impuestos administrados por el Gobierno Autónomo Descentralizado del cantón Junín - Párraga Pisco, Angie Lisbeth (2024)
The study was developed under the objective of analyzing the collection management of the sectional tax portfolio in the Gobierno Autónomo Descentralizado (GAD) of the canton Junín in the period 2019 - 2022 for the improvement of the collection process. Methodologies were implemented according to the types of research, supported by inductive and deductive methods and instruments such as interviews and synthetic analysis, in addition, management indicators were implemented to identify the levels of efficiency in tax collection, an Ishikawa diagram to identify root causes of the problems and the improvement plan to address the deficiencies detected. The results show average delinquency rates of 70% in the periods analysed, this is related to the portfolio recovery efficiency rates obtained which vary from 31% to 27%, the historical review of collection shows that the taxes that contribute most are non-budgeted revenues in taxes and valued species, urban properties have 57% average compliance and valued species reach 100%, in contrast, budgeted taxes average 31%, rustic properties 15% and rates 0%, being the least effective in collection, all these factors are related to the lack of effectiveness in collection management, lack of payment culture and communication problems.